PENGARUH METODE TUTOR SEBAYA DALAM PEMBELAJARAN KELAS V SD N MANGUNSARI 06 - Nova Dwi Setiana (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
Research on the effect of peer tutoring methods in 5th grade learning inSD Negeri Mangunsari 06 Salatiga city aims to find out how improvement in learning in students in using peer tutoring learning methods in the classroom and knowing the effect of peer tutoring learning method in 5th grade learning SD Negeri Mangunsari 06 Salatiga city. The research method used is the interview method. The results of the research that have been conducted are that students more active and creative thinking in the presence of peer tutoring methods. This means that there is an effect of increasing students learning interest with peer tutoring methods in learning. Therefore, in using peer tutoring learning methods more effective and fun for students.